Investigating the influence of fans on home advantage outcomes in association football across Europe - Bhagwandeen, B.; Mohammed, A.; Dialsingh, I. (Soccer & Society, 2024)
Fan support has long been stated as one of the major contributors to the home advantage which football teams enjoy across Europe; whereby fans motivate the home team to increase performance levels, and in some cases, inadvertently cause referees to subconsciously make decisions in favour of the home team. With the naturally created experimental design by the COVID-19 pandemic, the unique opportunity arose to analyse the influence of fans on these home advantage outcomes. Mixed-effects models were used while controlling for available confounds. It was observed that home teams won fewer points and were less dominant without the support of their fans; while referees called more fouls against, and produced more yellow cards for home teams without fans present. However, these decisions were dependent on team dominance in a match. The findings reinforced social theories and also provided greater insights into the home advantage phenomenon.